Impact of simulated rainfall on persistence of fungicides used against late blight (Phytophthora infestans) of tomato (Solanum lycopersicum) - RANI, RITU; SHARMA, VINEET K; KUMAR, PARDEEP; MOHAN, C (The Indian Journal of Agricultural Sciences, 2015)
Persistence of mancozeb 75%WP and metalaxyl 8%+mancozeb 64 %WP fungicides was studied on tomato (Solanum lycopersicum L.) leaves with respect to different simulated rain amounts (0, 5, 10 and 15mm) after different number of days (0, 2, 4, 6, 8 and 10) after fungicidal spray. Rainfall applied immediately after fungicidal spray removed fungicides from the leaf surface resulting in higher disease severity. As rain amount increased from 5 to 15 mm, disease was also increased in both the test fungicides. In case of metalaxyl 8%+mancozeb 64 %WP @ 0.25 per cent, disease severity was less as compared to the mancozeb 75%WP @ 0.25 per cent. The delaying of rainfall by 2 days after fungicidal spray resulted in significant reduction in disease severity in case of metalaxyl 8%+mancozeb 64 %WP sprayed tomato plants. Metalaxyl 8%+mancozeb 64%WP being a systemic fungicide was absorbed into the system of the plant. However, this was not true in case of mancozeb 75%WP sprayed tomato plants. Since, mancozeb 75 %WP a non systemic fungicide was washed with the application of rain.